Needs Analysis of an Integrated Android-Based Academic Information System in Higher Education - Kaprawi Rahman; Arismunandar; Nurhikmah H; Abdul Hakim (CV. Media Digital Publikasi Indonesia, 2025)
This study aims to analyze the needs for an integrated academic information system based on Android and web technology at the Master of Educational Technology Program, Graduate School of Universitas Negeri Makassar. The research employed a descriptive qualitative method, involving 30 students, 5 lecturers, and 2 administrative staff as purposive participants. Data were collected through observation, semi-structured interviews, questionnaires, and document analysis. Findings revealed that the current academic system is still static, unresponsive, and lacks interactivity, resulting in limited accessibility and inefficient communication. More than 85% of students expressed the need for a mobile-friendly platform that supports academic service tracking, notifications, schedule access, and grade viewing. In addition, lecturers highlighted the importance of features such as uploading learning materials and evaluation results through the system. Based on triangulated data, users require a system with real-time notifications, personal dashboards, online academic forms, and Android-web integration. This aligns with recent international studies emphasizing the role of mobile academic systems in increasing engagement, transparency, and operational efficiency. The research recommends the immediate development of an Android-based academic information system using a user-centered design approach to ensure system relevance and usability. The results of this study can serve as a reference for institutions aiming to implement digital transformation in higher education academic services.